1996
DOI: 10.1016/s0092-8674(00)81030-2
|View full text |Cite
|
Sign up to set email alerts
|

H2-M Mutant Mice Are Defective in the Peptide Loading of Class II Molecules, Antigen Presentation, and T Cell Repertoire Selection

Abstract: H2-M is a nonconventional major histocompatibility complex (MHC) class II molecule that has been implicated in the loading of peptides onto conventional class II molecules. We generated mice with a targeted mutation in the H2-Ma gene, which encodes a subunit for H2-M. Although the mutant mice express normal class II cell surface levels, these are structurally distinct from the compact SDS-resistant complexes expressed by wild-type cells and are predominantly bound by class II-associated invariant chain peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
269
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(282 citation statements)
references
References 44 publications
12
269
0
1
Order By: Relevance
“…The DMa-deficient mice (22), on a (129 ϫ C57BL/6)F 2 background, that express the H-2 b haplotype, have been maintained by brother-sister matings. The production of Ii chain mutants (33), and sublines established by backcrossing the targeted allele onto BALB/cAn (H-2 d ), or B.C-9, a strain congenic with C57BL/6, but expressing the Igh a allotype of BALB/c, has been described (10,34).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DMa-deficient mice (22), on a (129 ϫ C57BL/6)F 2 background, that express the H-2 b haplotype, have been maintained by brother-sister matings. The production of Ii chain mutants (33), and sublines established by backcrossing the targeted allele onto BALB/cAn (H-2 d ), or B.C-9, a strain congenic with C57BL/6, but expressing the Igh a allotype of BALB/c, has been described (10,34).…”
Section: Animalsmentioning
confidence: 99%
“…It also seems likely that DM actions demonstrated via these complementation assays could be influenced by many additional experimental parameters, such as abnormal expression levels and functional contributions by recipient cell lines, making it difficult to assess the significance of these observations. Current thinking about the class II pathway has been strongly influenced by studies of DM mutant mice (22)(23)(24). The loss of DM function disrupts conventional Ag presentation and causes complex defects with respect to selection of mature CD4 ϩ T cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, other data suggested that positive selection is not greatly impacted by the specificity of the self peptides presented. Here, the experimental approaches were designed to limit the available peptide/ MHC repertoire to one face and to examine the impact on repertoire size (15)(16)(17)(18). It was shown that in such "single" peptide/MHC mice, a large and diverse repertoire was selected.…”
Section: Positive Selection Is Limited By Available Peptide-dependentmentioning
confidence: 99%
“…These co-players of antigen processing are Ii, MHC encoded DM and DO molecules and certain proteases. [1][2][3][4][5][6][7] An important role of Ii is to escort class II molecules to the endocytic route where Ii is degraded by cathepsin S or cathepsin L in MIIC vesicles. 7,8 Along the transition from multivesicular to multilaminar MIICs, DM releases the remaining Ii fragment CLIP (class II-associated Ii peptides) from class II dimers and catalyzes the uptake of antigenic peptides.…”
Section: Introductionmentioning
confidence: 99%